The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3847/1538-4357/abee1a
|View full text |Cite
|
Sign up to set email alerts
|

Observational Signatures of Cosmic-Ray Interactions in Molecular Clouds

Abstract: We investigate ionization and heating of gas in the dense, shielded clumps/cores of molecular clouds bathed by an influx of energetic, charged cosmic rays (CRs). These molecular clouds have complex structures, with substantial variation in their physical properties over a wide range of length scales. The propagation and distribution of CRs is thus regulated accordingly, in particular, by the magnetic fields threaded through the clouds and into the dense regions within. We have found that a specific heating rat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 236 publications
3
16
1
Order By: Relevance
“…In this section, we probe 6.4 keV line emissions from different cloud regions, toward understanding LECR populations within Sgr B2 in the context of both ambient LECRs in the CMZ and LECR production in the cloud. The problem of CR transport into and within MCs is model dependent and has been the subject of several theoretical works with different predictions for the geometry of energy deposition by LECRs, all of which necessarily make simplifying assumptions about the gas distribution and magnetic field structure, for either a generic cloud or Sgr B2 specifically (Dogiel et al 2015;Morlino & Gabici 2015;Gabici 2013;Owen et al 2021).…”
Section: Low-energy Cosmic Ray Limitsmentioning
confidence: 99%
“…In this section, we probe 6.4 keV line emissions from different cloud regions, toward understanding LECR populations within Sgr B2 in the context of both ambient LECRs in the CMZ and LECR production in the cloud. The problem of CR transport into and within MCs is model dependent and has been the subject of several theoretical works with different predictions for the geometry of energy deposition by LECRs, all of which necessarily make simplifying assumptions about the gas distribution and magnetic field structure, for either a generic cloud or Sgr B2 specifically (Dogiel et al 2015;Morlino & Gabici 2015;Gabici 2013;Owen et al 2021).…”
Section: Low-energy Cosmic Ray Limitsmentioning
confidence: 99%
“…Within the Milky Way, cosmic-ray transport studies and observations have indicated an average diffusion coefficient between D 0 = 10 28 -3 × 10 28 cm 2 s −1 (Evoli et al 2020). However, regarding the dense gas, studies have shown a spread over several orders of magnitude, from D 0 = 10 27 -10 30 cm 2 s −1 (Dogiel et al 2015;Owen et al 2021). As such, it is even more paramount to understand what is constraining the CR transport within molecular gas, and how the local environment changes the diffusion coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of spectral model is discussed in detail in [6], however its exact form (if reasonable) does not substantially affect the results of this work. The diffusive term ∇ • [𝐷 (𝐸, 𝒔)∇𝑛] is governed by the coefficient 𝐷 (𝐸, 𝒔) which depends on the gyro-scattering radius (or frequency) of the CRs of energy 𝐸 in their local magnetic field, as well as turbulence and magnetohydrodynamical (MHD) perturbations along local magnetic field vectors.…”
Section: Cr Propagation In MC Complexesmentioning
confidence: 99%
“…Here 𝜆 1 = 𝜆 td (|𝜔 L |/𝜔 p,0 ) is the CR resonant scattering length scale parallel to the background magnetic field line. The turbulent decay length scale is 𝜆 td ≈ 𝑣 A 𝜏 td , (where we use 𝜏 td = 2 Myrfor discussion, see [6]). The CR gyro-frequency is 𝜔 L , with a sign convention set by the charge (in units of proton charge).…”
Section: Empirical Diffusion Parametermentioning
confidence: 99%
See 1 more Smart Citation